رسواکی ناول نگاری کانفسیاتی تناظر: Ruswa ki Novel Nigari ka Nafsiyati Tanazur - Siddique , Dr. Arif; Fayzi , Prof. Dr. Fayyaz Ahmed (Zoraiz, 2025)
Literature and Psychology are closely related. The inner feelings and Psychology of the characters influence their behavior. When a novelist adapts various political and social events in a novel, the psychological study of his characters proves helpful in understanding the Novel. An effort has been made through this article to understand the inner feelings of Mirza Hadi Ruswa’s characters while highlighting the psychological aspects of his novels.